Rare earth elements as emerging contaminants: Multi-source release, geochemical tracing, and implications for environmental monitoring and management - Yong-He Han; Ming-Zhu Zou; Dong-Xing Guan; Yi-Xi Li; Ping Xiang; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

Temporal dynamics and synergistic pollution of microplastics and heavy metal(loid)s in subtropical mangrove sediments - Shuting Qin; Li Shang; Jiawei Liao; Ismail Khan; Xingyun Huang; Yingwen Li; Lulu Zhang; Faming Wang; Bi Zou; Ping Zhuang (Gondwana Research, 2026)

Unlocking catalytic capacity of (S)-selective ω-transaminases toward aryl methyl ketones via pocket engineering and droplet screening - Ping Gui; Xiao Li; Wangtao Jiang; Ruolin Yang; Peiyao Chang; Xingwang Qie; Xinrui Wang; Xuefeng Wang; Jingjie Jiang; Liyan Wang; Xiaojie Guo; Hongbin Zou; et al. (Bioresource Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Metabolites from Trichoderma amazonicum AF2115A by monoculture and coculture with Fusarium oxysporum A11F(B) - Wei-Cheng Xu; Yin-Ping Song; Ji-Xue Zou; Xiu-Li Yin; Nai-Yun Ji (Phytochemistry, 2026)

Paleoseismic activity revealed from soft sediment deformation structures in the Eastern Himalayan Syntaxis since the Last Glacial Maximum - Huiying Wang; Ping Wang; Gang Hu; Zinan Zou; Wenqiao Li; Chao Xie (Journal of Asian Earth Sciences, 2026)

TGase-induced WPI-GA microgels for stabilized HIPEs and encapsulation probiotics with enhanced thermal stability and gastrointestinal survival - Yaxin Yin; Yingnan Zou; Chin Ping Tan; Deyang Li; Xiaojiao Zheng; Daodong Pan; Maolin Tu (Food Hydrocolloids, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Spatial confinement of N atoms by interfacing doping on ZnIn2S4 nanosheets to enhance built-internal electric field for photocatalytic water splitting - Shuqu Zhang; Lixia Yang; Ren-Jie Song; Minhao Li; Jian-Ping Zou; Shenglian Luo (Chemical Engineering Journal, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Gamma-gliadins and some non-gluten proteins critically influence the rheological behavior of wheat dough subjected to thermal treatment - Ping Li; Pai Peng; Xiaoyang Zou; Xinrui Ren; Xinyu Zhang; Wen Zhao; Xinyu Kou; Yu Liu; Xinzhong Hu; Xiaolong Wang (Food Hydrocolloids, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Cultivar-dependent effects of arbuscular mycorrhizal (AM) fungal inoculation on fruit quality and native AM fungal community in navel orange - Xin-Ping Tan; Cheng-Zhuo Li; Ying-Ning Zou; An-Qi Lei; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Corynoline promotes apoptosis and inhibits proliferation of glioblastoma via regulating the STAT3/Bcl-2 signalling pathway - Yu Xiong; Wenyuan Ji; Jianjun Zhou; Shenghua Liu; Lusheng Li; Xuan Zhai; Bin Zou; Ligang Chen; Ping Liang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Advanced technologies of artery-on-a-chip: a review of construction strategies and disease models - Shi-Qi Chang; Li Qiao; Oluwatosin David Abodunrin; Lin Zou; Ning-Ping Huang (Angiogenesis, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Tracing monomethylmercury origins in planktivorous migratory fish in the coastal East China Sea: Evidences from mercury and carbon stable isotopes - Chenxi Zou; Rui Wang; Ping Li; Shaochen Yang; Haiyu Yan; Daqiang Yin (Journal of Hazardous Materials, 2026)

Inverted conical pore array construction by one-step electrodeposition for 3D self-supported electrode to boost mass transfer in hydrogen evolution reaction - Linghan Lan; Yaxing Zhu; Juchao Liang; Shaolong Wang; Yanan Zou; Zhuo Li; Yang Yang; Ping Zhang (Fuel, 2026)

Analysis of the time-varying reliability of earth dam slopes considering multiparameter spatial variability - Zhi-Ping Deng; Yi Zou; Wenqi Du; Dian-Qing Li; Mao-Xin Wang; Shui-Hua Jiang (Computers and Geotechnics, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Inhibitory Effect of TrxR Inhibitor Ag (Ⅰ) Schiff Base Complex Against Cervical Cancer Via ROS-mediated ASK1/MAPK Signaling and Autophagy - Jian-Jun Liu; Jia-Hua Zou; Bin Dong; Xue-Ping Lu; Li-Feng Chen; San-Mei Ma; Zhong Liu (Biological Trace Element Research, 2025)

The role of mineralization bacteria in the immobilization of cadmium and lead in aqueous solutions - Ismail Khan; Mimi Wang; Li Shang; Bi Zou; Yingwen Li; Yongxing Li; Zhe Lu; Lulu Zhang; Faming Wang; Abdul Rehman; Ping Zhuang (Journal of Hazardous Materials, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Novel T–U-Shaped Barge Design and Dynamic Response Analysis for Float-Over Installation of Offshore Converter Platform - Ping Li; Li Zhao; Mingjun Ouyang; Kai Ye; Rui Zhao; Meiyan Zou; Mingsheng Chen (Journal of Marine Science and Engineering, 2025)
To address the current lack of specialized equipment for offshore wind platform installation and the unresolved challenges in deploying large offshore converter stations, this paper proposes a novel T–U-shaped barge for large offshore wind structures. First, a hydrodynamic model of the T–U-shaped barge is constructed and analyzed in ANSYS-AQWA. The influence of resonance occurring in the gap at the U-shaped stern on the frequency-domain model of the T–U-shaped barge is investigated. Subsequently, two installation configurations are examined: loading at the bow and loading at the stern of the T–U-shaped barge. This study comprehensively considers key components of the float-over installation system, including leg mating units (LMUs), deck support units (DSUs), fenders, and mooring cables. The results show that, for both installation schemes, the dynamic load distribution on each LMU evolves as the load-transfer stage progresses, and the sensitivity to wave period varies across different load-transfer stages, even under the same operating condition. This study evaluates the performance of the proposed T–U-shaped barge in the float-over installation of large offshore converter stations, demonstrating that its distinctive configuration endows it with strong functionality and provides valuable references for optimizing offshore wind-structure installation methods, as well as for the design and manufacturing of installation equipment.

Observer-Based Robust Control for Dynamic Positioning in Float-Over Installation of Offshore Converter Stations - Ping Li; Li Zhao; Mingjun Ouyang; Jinghao Zhao; Rui Zhao; Meiyan Zou; Mingsheng Chen (Journal of Marine Science and Engineering, 2025)
With the development of offshore wind power progressing towards larger-scale and deeper-water projects, the float-over installation of offshore converter stations has become a mainstream solution due to its high carrying capacity, efficiency and cost-effectiveness. This study addresses the dynamic positioning (DP) challenges during this operation, where traditional PID controllers often struggle with performance under complex environmental loads. An Observer-Based Robust Controller (OBRC) is proposed and integrated with a constant parameter time-domain model (CPTDM) to simulate the DP process of a novel T-U barge. Time-domain simulations for both standby and entry phases were conducted under various wave directions and periods. The results demonstrate that the OBRC significantly outperforms the conventional PID controller in maintaining positioning accuracy. The findings provide critical insights into motion responses and control strategies, offering valuable guidance for the design and safe operation of future float-over installations.

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Metabolic mechanism of a novel carboxylesterase YvaK in Priestia aryabhattai DPX-1 for carbamate insecticide indoxacarb detoxification - Ping Zou; Zijing Li; Shengyang Li; Yuehan Geng; Xin Ma; Xiangwei Wu; Rimao Hua; Liancheng Fang (Journal of Hazardous Materials, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Corrigendum to “Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum” [J. Trace Elem. Med. Biol. 87 (2025) 127580] - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

Ultra-low temperature removal of element mercury in coal-fired flue gas by activated carbon - Renjie Zou; Tong Sun; Guangqian Luo; Lingxuan Chen; Li Wang; Sheng Chen; Shiqing Wang; Xian Li; Ping Xiao; Hong Yao (Fuel, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Insights into mantle metasomatism during oceanic subduction from late Paleozoic (∼260 Ma) high-Mg diorites in the northeastern Tibetan Plateau - Feng-Hui Zou; Jian-Ping Zheng; Cai-Lai Wu; Chang-Qian Ma; Li-Huan Deng (Chemical Geology, 2025)

A new method of automatic microcharcoal identification and its demonstration in revealing the spatial heterogeneity of fire over the past 40,000 years in China - Yaguo Zou; Yunfa Miao; Yimin Li; Zisha Wang; Ziyue Zhang; Yongtao Zhao; Gaihong Niu; Ping Zhang; Yan Nie (Quaternary International, 2025)

Structural integrity and near-infrared absorption of the LH1 complex of Thermochromatium tepidum: Influence from the C-terminal lysine residues of LH1 α-polypeptide - Yi-Hao Yan; Yu-Qian Li; Mei-Juan Zou; Long-Jiang Yu; Jian-Ping Zhang (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

Aquaculture source of atmospheric N2O in China: Comparison of system types, management practices and measurement methods - Yifei Zhang; Guanghui Zhao; Ping Yang; Changchun Song; Yang Wang; Yiwen Zhang; Yuxing Zou; Zhuangpeng Zheng; Kam W. Tang; Siyue Li (Environmental Research, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Model the evolutionary pattern of N species and pool size in groundwater continuum by utilizing measured source and sink rates of nitrate and ammonium - Li-Li Han; Lianghao Ge; Ehui Tan; Wenbin Zou; Li Tian; Ping Li; Min Nina Xu; Shuh-Ji Kao (Journal of Hazardous Materials, 2024)

Simultaneously inhibit cadmium and arsenic uptake in rice (Oryza sativa L.) by Selenium enhanced iron plaque: Performance and mechanism - Peicheng Huang; Dan Zou; Chunhua Dong; Chongjian Tang; Qingzhu Li; Pengwei Zhao; Ping Zhang; Qi Liao; Zhihui Yang (Chemosphere, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

The composition of soil fungal communities is more dependent on biocrust type than on shrub cover in the Mu Us Desert - Lin Xu; Chaonan Li; Wenjun Xiong; YongPing Kou; Ping Zou; Bingjie Jiao; Minjie Yao; Junming Wang; Bingchang Zhang; Xiangzhen Li (Fungal Ecology, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Hybrid origin and hybrid status of the endangered Ilex sanqingshanensis revealed by molecular and morphological evidence - Wei-li Liu; Dan-qi Li; Yi-ping Zou; Ming-zhuo Hao; Zhi-yong Zhang; Deng-mei Fan; Yi Yang (Plant Systematics and Evolution, 2024)

Rainstorm and strong wind weathers largely increase greenhouse gases flux in shallow ponds - Yifei Zhang; Ping Yang; Yang Wang; Guanghui Zhao; Zhuangpeng Zheng; Yuxing Zou; Yiwen Zhang; Siyue Li (Science of The Total Environment, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Manganese-induced neurological pyroptosis: Unveiling the mechanism through the ROS activaed Caspase-3/GSDME signaling pathway - Jiacheng He; Xiaoli Ma; Jie Zhang; Yi-ping Yang; Huiyan Qin; Hao Chen; Shengtao Wei; Fangfei Li; Jian Wang; Guiqiang Liang; Yunfeng Zou (Food and Chemical Toxicology, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Warming and wetting-induced soil acidification triggers methanotrophic diversity loss and species turnover in an alpine ecosystem - Chaonan Li; Changting Wang; Ping Zou; Lin Xu; Haijun Liao; Nan Lan; Li Lei; Wenjun Xiong; Weidong Kong; Junming Wang; Xiangzhen Li (CATENA, 2024)

Co-application of chitooligosaccharides and arbuscular mycorrhiza fungi reduced greenhouse gas fluxes in saline soil by improving the rhizosphere microecology of soybean - Junqing Ma; Yi Xie; Jiali Sun; Ping Zou; Siqi Ma; Yuan Yuan; Shakeel Ahmad; Xia Yang; Changliang Jing; Yiqiang Li (Journal of Environmental Management, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

Nitrogen removal performances and metabolic mechanisms of denitrification systems using different volatile fatty acids as external carbon sources - Xin Li; Xiangzhen Li; Chaonan Li; Na Li; Ping Zou; Xiaolong Gao; Qin Cao (Chemical Engineering Journal, 2023)

Biotrophic interactions between plant and endophytic bacteria in removal of PAHs and Cd from contaminated soils enhanced by graphene oxide - Lingmei Li; Rui Liu; Jianjun Chen; Peidong Tai; Xiaoyi Bi; Ping Zou; Yajie Wang; Yao Xiao (Journal of Cleaner Production, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Porphyrin-based donor with asymmetric ending groups enables 16.31% efficiency for ternary all-small-molecule organic solar cells - Haojiang Shen; Yixuan Xu; Wentao Zou; Wenqing Zhang; Jianfeng Li; Ping Cai; Yuan Guo; Huajun Xu; Xiaotao Hao; Yanna Sun; Yuanyuan Kan; Yingguo Yang; et al. (Chemical Engineering Journal, 2023)

Cooperative strategy for pursuit-evasion problem in the presence of static and dynamic obstacles - Zhiyuan Sun; Hanbing Sun; Ping Li; Jin Zou (Ocean Engineering, 2023)

CircBLNK regulates tumor proliferation and apoptosis by miR-578/ING5 axis in non-small cell lung cancer - Ping Li; Liuyi Zou; Zuojun Luo; Yuhua Lu; Shuang Yu; Yujun Zhu; Yong Xie (Molecular & Cellular Toxicology, 2023)

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

A genome-wide co-expression network analysis revealed ZmNRAMP6-mediated regulatory pathway involved in maize tolerance to lead stress - Peng Liu; Li Jiang; Ping Long; Qinglin Li; Fengxia Hou; Guangsheng Yuan; Zhong Chen; Minyan Zhang; Chaoying Zou; Guangtang Pan; Langlang Ma; Yaou Shen (Theoretical and Applied Genetics, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Internal erosion of debris-flow deposits triggered by seepage - Xiangang Jiang; Anders Wörman; Xiaoqing Chen; Zhanyuan Zhu; Zuyin Zou; Weimin Xiao; Ping Li; Guojun Liu; Diyin Kang (Engineering Geology, 2023)

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

Soil particle size fractions affect arsenic (As) release and speciation: Insights into dissolved organic matter and functional genes - Qi Zou; Hang Wei; Zhiliang Chen; Ping Ye; Jianqiang Zhang; Mengqiang Sun; Ling Huang; Jing Li (Journal of Hazardous Materials, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

Effects of Elevation on Ecological Stoichiometry of Plant Leaves, Litter, and Soils in Pseudotsuga sinensis Forest in the Karst Mountain region, Southwest China - He Bin; Qing Li; Ping Zhang; Wangjun Li; Xiaohui Xue; Shun Zou; Qunsheng Zhang (Journal of Soil Science and Plant Nutrition, 2022)

Formation Control of Multiple Underactuated Surface Vessels with a Disturbance Observer - Zhiyuan Sun; Hanbing Sun; Ping Li; Jin Zou (Journal of Marine Science and Engineering, 2022)
To maintain the formation of underactuated surface vessels (USVs), this study designs a formation controller based on a virtual structure strategy. The problem of formation control is transformed into the problems of tracking the USV position and the virtual structure point position. Meanwhile, to eliminate the effects of model parameter uncertainties and external environment disturbances on USV tracking control, a compensation control algorithm based on disturbance estimation is proposed. The Lyapunov theorem is introduced to ensure that the trajectory tracking error of the proposed control algorithm eventually converges to any small region, which confirms global stability of the designed tracking error. The simulation results demonstrate that the proposed controller can eliminate the effect of external uncertain interference and maintain the formation of multiple USVs.

Self-Organizing Cooperative Pursuit Strategy for Multi-USV with Dynamic Obstacle Ships - Zhiyuan Sun; Hanbing Sun; Ping Li; Jin Zou (Journal of Marine Science and Engineering, 2022)
A self-organizing cooperation strategy for multiple unmanned surface vessels (USVs) to pursue intelligent evaders in the case of a dynamic obstacle vessel is proposed. Firstly, a self-organizing cooperative hunting strategy is proposed to form an Apollonius circle. According to the escape strategies of evaders under different encirclement states, the pursuers are divided into pursuit group and ambush group. The pursuit group drives the evaders into the ambush area and completes the encirclement together with the ambush group. In order to better deal with the dynamic obstacle ships encountered in the pursuit process in the dynamic ocean environment, the artificial potential field-based collision avoidance method for inter-USV and dynamic collision avoidance strategy for encountering obstacle ships based on International Regulations for Preventing Collisions at Sea (COLREGs) are proposed. The simulation results show that the algorithm can make the pursuers complete the encirclement of the evaders and has good obstacle avoidance performance and flexibility in the environment with dynamic obstacle ships.

Dynamics of nitrogen and phosphorus profile and its driving forces in a subtropical deep reservoir - Cunli Li; Ping Zhang; Guangwei Zhu; Chao Chen; Yucheng Wang; Mengyuan Zhu; Hai Xu; Cuiling Jiang; Wei Zou; Pengcheng Shi; Qing Zheng (Environmental Science and Pollution Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Scalp Acupuncture Protects Against Neuronal Ferroptosis by Activating The p62-Keap1-Nrf2 Pathway in Rat Models of Intracranial Haemorrhage - Ming-Yue Li; Xiao-Hong Dai; Xue-Ping Yu; Wei Zou; Wei Teng; Peng Liu; Xin-Yang Yu; Qi An; Xin Wen (Journal of Molecular Neuroscience, 2022)
Intracerebral haemorrhage (ICH) can be a catastrophic event; even if the initial stages of the pathology were well-managed, a number of patients experience varied residual neurological deficits following the insult. Ferroptosis is a recently identified type of cell demise which is tightly linked to the neurological impairment associated with ICH. In the current work, the prophylactic impact of scalp acupuncture (SA) therapy on autologous blood injection murine models of ICH was investigated in order to establish whether SA could mitigate the secondary damage arising following ICH by moderating ferroptosis. The pathophysiological mechanisms associated with this process were also explored. Ludmila Belayev tests were utilised for the characterisation of neurological damage. Haematoxylin–eosin staining was employed in order to determine the cerebral impact of the induced ICH. Malondialdehyde (MDA) and iron titres in peri-haemorrhagic cerebral tissues were appraised using purchased assay kits. Transmission electron microscopy delineated mitochondrial appearances within nerve cell bodies from the area of haemorrhage. Western blotting techniques were utilised to assay the degree of protein expression of NeuN, sequestosome 1 (p62), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1). The frequencies of Nrf2, GPX4 and FTH1 positive cells, respectively, were documented with immunohistochemical staining. The results demonstrated that therapy with SA after ICH mitigated MDA and iron sequestration, diminished the appearance of contracted mitochondria with increased outer mitochondrial membrane diameter within the nerve cell bodies, and suppressed neuronal ferroptosis. The pathways responsible for these effects may encompass amplified p62, Nrf2, GPX4 and FTH1 expression, together with decreased Keap1 expression. Application of SA reduced identified neurobehavioural abnormalities after ICH; no disparities were observed between the consequences of SA therapy and deferoxamine delivery. It can be surmised that intervention with SA enhanced recovery after ICH by triggering the antioxidant pathway, p62/Keap1/Nrf2, and causing FTH1 and GPX4 upregulation, factors that participate in diminishing excess iron and thus in mitigating lipid peroxidation insults arising from ferroptosis following ICH.

Homeostasis Regulation by Potassium Channel Subfamily K Member 3 (KCNK3) in Various Fishes - Zheng-Yong Wen; Chuan-Jie Qin; Yun-Yun Lv; Yan-Ping Li; Yuan-Chao Zou; Sheng-Tao Guo; Qiong Shi (Frontiers in Marine Science, 2021)
Potassium channels are important for K + transport and cell volume regulation, which play important roles in many biological processes such as hormone secretion, ion homeostasis, excitability, and cell development. In mammals, a total of 15 potassium channels were identified and they were divided into six subfamilies, including TALK (TALK1, TALK2, TASK2), TASK (TASK1, TASK3, TASK5), TREK (TREK1, TREK2, TRAAK), TWIK (TWIK1, TWIK2, KCNK7), THIK (THIK1, THIK2) and TRESK. TASK1, also known as potassium channel subfamily k member 3 (KCNK3), is the first member identified in the TASK subfamily. This K 2 P channel has potential applications in fish breeding and aquaculture industry due to its important roles in various physiological processes. Despite its functional role has been well studied in mammals; however, it is less known in fishes. In this review, we systematically summarize recent research advances of this critical potassium channel in representative fishes, such as gene number variation, tissue distribution, phylogeny, and potential homeostasis regulation role. This paper provides novel insights into the functional properties of these fish kcnk3 genes (including osmoregulation, energy homeostasis maintenance and fatty acids metabolism regulation), and also expands our knowledge about their variations among diverse fishes.

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

Resource utilization of organic spent adsorbent to prepare three-dimensional sulfate-functionalized layered double oxide for superior removal of azo dye - Lingjie Zhang; Siyin Zheng; Peng Li; Zhongbang Zhu; Youqin Zou; Ping Zhang (Environmental Science and Pollution Research, 2021)

Alpha-Lipoic Acid Attenuates Cadmium- and Lead-Induced Neurotoxicity by Inhibiting Both Endoplasmic-Reticulum Stress and Activation of Fas/FasL and Mitochondrial Apoptotic Pathways in Rat Cerebral Cortex - Yan Yuan; Shi Wen Zhao; Shuang Quan Wen; Qiao Ping Zhu; Li Wang; Hui Zou; Jian Hong Gu; Xue Zhong Liu; Jian Chun Bian; Zong Ping Liu (Neurotoxicity Research, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Restricted nitrous oxide emissions by ammonia oxidizers in two agricultural soils following excessive urea fertilization - Zhaoming Chen; Qiang Wang; Jun Zhao; Yudong Chen; Huoyan Wang; Junwei Ma; Ping Zou; Li Bao (Journal of Soils and Sediments, 2020)

Nitrate removal from groundwater using negatively charged nanofiltration membrane - Lianpei Zou; Sitong Zhang; Jianyong Liu; Yi Cao; Guangren Qian; Yu-You Li; Zhi Ping Xu (Environmental Science and Pollution Research, 2019)

Interseismic Coupling in the Central Nepalese Himalaya: Spatial Correlation with the 2015 Mw 7.9 Gorkha Earthquake - Shuiping Li; Qi Wang; Gang Chen; Ping He; Kaihua Ding; Yunguo Chen; Rong Zou (Pure and Applied Geophysics, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Study on Stability of Goaf Pillars in Daqiao Phosphate Mine: Theoretical Calculation and Field Investigation - Feifei Wang; Ping Zou; Zhonghua Meng; Aibing Li; Zhengyu Liu; Wanjie Hu; Zeng Ma (Geotechnical and Geological Engineering, 2019)

A geostatistic investigation of the comprehensive evaluation of fertility and spatial heterogeneity of forest soil nutrients in hilly and mountainous regions of southern China - Da-ping Song; Hong Li; Shan-jiang Liu; Guo-yuan Zou; Dong-sheng Liu (Arabian Journal of Geosciences, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Update on the clinical application of deep brain stimulation in sleep dysfunction of Parkinson’s disease - Shuang Zou; Yu-Long Lan; Ya-Ping Hu; Xiao-Xue Yin; Wen-Long Liu; Tao Li; Zhanhua Liang (Acta Neurologica Belgica, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Eriodictyol protects against Staphylococcus aureus-induced lung cell injury by inhibiting alpha-hemolysin expression - He Xuewen; Ouyang Ping; Yuan Zhongwei; Yin Zhongqiong; Fu Hualin; Lin Juchun; He Changliang; Shu Gang; Yuan Zhixiang; Song Xu; Zou Yuanfeng; Li Lixia; et al. (World Journal of Microbiology and Biotechnology, 2018)

OsPKS2 is required for rice male fertility by participating in pollen wall formation - Ting Zou; Mingxing Liu; Qiao Xiao; Tao Wang; Dan Chen; Tao Luo; Guoqiang Yuan; Qiao Li; Jun Zhu; Yueyang Liang; Qiming Deng; Shiquan Wang; et al. (Plant Cell Reports, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Oral bioaccessibility and human exposure assessment of cadmium and lead in market vegetables in the Pearl River Delta, South China - Ping Zhuang; Yingwen Li; Bi Zou; Feng Su; Chaosheng Zhang; Hui Mo; Zhian Li (Environmental Science and Pollution Research, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Demyelination and polycythemia in a case of paraganglioma - Xin-Bao Wang; Xiu-Yu Shi; Wen-Ze Wang; Guang Yang; Li-Ping Zou (Acta Neurologica Belgica, 2016)

Functional MRI in medulloblastoma survivors supports prophylactic reading intervention during tumor treatment - Ping Zou; Heather M. Conklin; Matthew A. Scoggins; Yimei Li; Xingyu Li; Melissa M. Jones; Shawna L. Palmer; Amar Gajjar; Robert J. Ogg (Brain Imaging and Behavior, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Rice grassy stunt virus nonstructural protein p5 serves as a viral suppressor of RNA silencing and interacts with nonstructural protein p3 - Chao Zhang; Xiao-juan Liu; Kang-cheng Wu; Lu-Ping Zheng; Zuo-mei Ding; Fei Li; Peng Zou; Liang Yang; Jian-guo Wu; Zu-jian Wu (Archives of Virology, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Identification of Mycoplasma suis MSG1 interaction proteins on porcine erythrocytes - Yaning Zhang; Yao Zou; Peipei Ma; Hassan Mushtaq Muhammad; Yufeng Li; Ping Jiang (Archives of Microbiology, 2015)

Contrasting effects of silicates on cadmium uptake by three dicotyledonous crops grown in contaminated soil - Huan-ping Lu; Ping Zhuang; Zhi-an Li; Yi-ping Tai; Bi Zou; Ying-wen Li; Murray B. McBride (Environmental Science and Pollution Research, 2014)

Purification of contaminated paddy fields by clean water irrigation over two decades - Yiping Tai; Huanping Lu; Zhian Li; Ping Zhuang; Bi Zou; Hanping Xia; Faming Wang; Gang Wang; Jun Duan; Jianxia Zhang (Environmental Geochemistry and Health, 2013)

Health risk assessment for consumption of fish originating from ponds near Dabaoshan mine, South China - Ping Zhuang; Zhi-an Li; Murray B. McBride; Bi Zou; Gang Wang (Environmental Science and Pollution Research, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Regulatory long non-coding RNA and its functions - Yong Huang; Ning Liu; Jian Ping Wang; Yu Qin Wang; Xue Li Yu; Zhan Bin Wang; Xiang Chao Cheng; Quan Zou (Journal of Physiology and Biochemistry, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Cloning and the expression pattern of Spätzle gene during embryonic development and bacterial challenge in Artemia sinica - Lu-ping Zheng; Lin Hou; Miao Yu; Xiang Li; Xiang-yang Zou (Molecular Biology Reports, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

H. pylori related proinflammatory cytokines contribute to the induction of miR-146a in human gastric epithelial cells - Na Li; Xiang Xu; Bin Xiao; En-Dong Zhu; Bo-sheng Li; Zhen Liu; Bin Tang; Quan-Ming Zou; Hua-Ping Liang; Xu-Hu Mao (Molecular Biology Reports, 2012)

The different expression of immune-related cytokine genes in response to velogenic and lentogenic Newcastle disease viruses infection in chicken peripheral blood - Wen-Quan Liu; Ming-Xing Tian; Yuan-Ping Wang; Yang Zhao; Nian-Li Zou; Fang-Fang Zhao; San-Jie Cao; Xin-Tian Wen; Ping Liu; Yong Huang (Molecular Biology Reports, 2012)

Transcriptional control of human CD2AP expression: the role of Sp1 and Sp3 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2012)

Xanthoceraside attenuates amyloid β peptide25–35-induced learning and memory impairments in mice - Ping Lu; Takayoshi Mamiya; Lingling Lu; Akihiro Mouri; Takashi Ikejima; Hyoung-Chum Kim; Li-Bo Zou; Toshitaka Nabeshima (Psychopharmacology, 2012)

Hemodynamic responses to visual stimulation in children with sickle cell anemia - Ping Zou; Kathleen J. Helton; Matthew Smeltzer; Chin-Shang Li; Heather M. Conklin; Amar Gajjar; Winfred C. Wang; Russell E. Ware; Robert J. Ogg (Brain Imaging and Behavior, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Reduced expression of netrin-1 is associated with fetal growth restriction - Wang Qian-hua; Zhong Shao-ping; Zhu Jian-wen; Yang Yun; Zou Li (Molecular and Cellular Biochemistry, 2011)

Direct repression of the human IRF-3 promoter by E2F1 - Hua-Guo Xu; Wei Ren; Li Zou; Yi Wang; Rui Jin; Guo-Ping Zhou (Immunogenetics, 2011)

Genetic analysis revealed LX4 genotype strains of avian infectious bronchitis virus became predominant in recent years in Sichuan area, China - Nian-Li Zou; Fang-Fang Zhao; Yuan-Ping Wang; Ping Liu; San-Jie Cao; Xin-Tian Wen; Yong Huang (Virus Genes, 2010)

Incidence and risk of significantly raised blood pressure in cancer patients treated with bevacizumab: an updated meta-analysis - Mao Mao An; Zui Zou; Hui Shen; Ping Liu; Meng Li Chen; Yong Bing Cao; Yuan Ying Jiang (European Journal of Clinical Pharmacology, 2010)

Effects of soil amendment with different carbon sources and other factors on the bioremediation of an aged PAH-contaminated soil - Ying Teng; Yongming Luo; Lifeng Ping; Dexun Zou; Zhengao Li; Peter Christie (Biodegradation, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Prevalence of human metapneumovirus in hospitalized children with respiratory tract infections in Tianjin, China - Xiao-yan Li; Jin-ying Chen; Mei Kong; Xu Su; Yan-ping Yi; Ming Zou; Hua Zhang (Archives of Virology, 2009)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Litterfall Dynamics of an Evergreen Broadleaf Forest and a Pine Forest in the Subtropical Region of China - Zhi An Li; Bi Zou; Han-ping Xia; Hai Ren; Jiang-ming Mo; Hong Weng (Forest Science, 2005)
Monthly litterfall was monitored over a 10-year period from an evergreen broadleaf forest (EBF) and a pine forest (PF) in subtropical South China. During this period, litter was also collected bimonthly from the forest floor for 2 years. Total annual litterfall in EBF fluctuated around 9 Mg ha−1 with leaves, branches, and miscellanea accounting for 52.5%, 22.2%, and 25.3%, respectively. Total annual litterfall alternated between high and low values in consecutive years. Storms and pest outbreaks were responsible for most of the peaks in both monthly and annual litterfall. Litter from each of 43 species was recorded, but 9 species contributed about 85% of total litterfall. Dominant species shed their leaves in a more regular pattern with peaks mainly from Jan. to Mar. Pine forest (Pinus massoniana) produced much less litterfall than EBF, with a mean of 2.7 Mg ha−1. Here, leaves accounted for 73.2% of total litterfall, branches only 11.4%, and miscellanea 15.4%. Litter on the ground amounted to 5.2 Mg ha−1 in EBF and 2.9 Mg ha−1 in PF. The results show that this climax forest has much higher litterfall and forest floor mass than the pine forest, and litterfall is rather stable with regard to annual variation. FOR. SCI. 51(6):608–615.